2000
DOI: 10.1074/jbc.m005095200
|View full text |Cite
|
Sign up to set email alerts
|

Separating Substrate Recognition from Base Hydrolysis in Human Thymine DNA Glycosylase by Mutational Analysis

Abstract: Human thymine DNA glycosylase (TDG) was discovered as an enzyme that can initiate base excision repair at sites of 5-methylcytosine-or cytosine deamination in DNA by its ability to release thymine or uracil from G⅐T and G⅐U mismatches. Crystal structure analysis of an Escherichia coli homologue identified conserved amino acid residues that are critical for its substrate recognition/interaction and base hydrolysis functions. Guided by this revelation, we performed a mutational study of structure function relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 21 publications
12
163
3
Order By: Relevance
“…A key question regarding the catalytic mechanism of DNA glycosylases is how they bind and position the nucleophilic water molecule. Previous structural studies indicated that Asn18 of Escherichia coli MUG coordinates the nucleophile (33,34), and biochemical studies showed that the corresponding residue in TDG, Asn140, is essential for G·T glycosylase activity, consistent with a major role in catalysis (19,35). Although a mechanism of nucleophile binding involving the catalytic Asn was proposed for MUG and TDG enzymes (33), it has remained unsubstantiated because a putative nucleophilic water molecule has not been directly observed in any of the existing DNA-bound structures of TDG or MUG enzymes (29,33,34).…”
Section: Resultsmentioning
confidence: 96%
“…A key question regarding the catalytic mechanism of DNA glycosylases is how they bind and position the nucleophilic water molecule. Previous structural studies indicated that Asn18 of Escherichia coli MUG coordinates the nucleophile (33,34), and biochemical studies showed that the corresponding residue in TDG, Asn140, is essential for G·T glycosylase activity, consistent with a major role in catalysis (19,35). Although a mechanism of nucleophile binding involving the catalytic Asn was proposed for MUG and TDG enzymes (33), it has remained unsubstantiated because a putative nucleophilic water molecule has not been directly observed in any of the existing DNA-bound structures of TDG or MUG enzymes (29,33,34).…”
Section: Resultsmentioning
confidence: 96%
“…The influence of UDG activity on sensitivity to thymidylate deprivation in S. cerevisiae appeared to be transient [24,26]. S. cerevisiae lack SMUG1, MBD4, and TDG homologues [27], all of which are reported to remove uracil and 5-FU at least in vitro [8,10,11]. The absence of APN1, the major AP endonuclease in S. cerevisiae, leads to heightened sensitivity to 5-FU or antifolates [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the SMUG1 DNA glycosylase can remove 5-FU from DNA and that this activity protects MEFs from 5-FU toxicity [8]. Interpreting the causes of 5-FU toxicity is complicated by the fact that 5-FU incorporated into DNA can be recognized by mismatch repair [9], and two additional DNA glycosylases of BER, namely TDG and MBD4 [10,11]. Thus, the precise role of BER during thymidylate deprivation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The rate-limiting step in the mechanism in vitro is the release of the product (e.g. G : AP-site) due to rigid hydrogen bonding interactions between the enzyme and the Watson-Crick face of the guanine opposite the AP-site (Hardeland et al, 2000). This shields the cytotoxic APsite until the next enzyme in the pathway, APendonuclease APE1 (also called HAP1) enters.…”
Section: Identification Of Tdg and Biochemical Propertiesmentioning
confidence: 99%